Gut microbiota affects aneurysms through biomechanical mechanisms: A mendelian randomization study - Li, Renjie; Xu, Yi; Cheng, Tao (Molecular & Cellular Biomechanics, 2024)
Purpose: To assess any potential associations between gut microbiota (GM) and aortic aneurysm and cerebral aneurysm in biomechanics (AA and CA). Methods: We performed a two-sample Mendelian randomization (MR) to assess the causal association between GM and AA, CA. The inverse-variance weighted (IVW) model was used as the main analytical method and was followed by sensitivity analysis, including heterogeneity test, horizontal pleiotropy test, and leave-one-out analysis, to appraise the robustness of the MR results. Results: Our IVW results showed that RuminococcaceaeUCG005 [OR = 1.43, 95% CI (1.17,1.76), P = 0.000] and Roseburia [OR = 1.16, 95% CI (1.00,1.34), P = 0.049] were positively associated with AA, while Prevotella9 [OR = 0.81, 95% CI (0.68,0.96), P = 0.022] and RuminococcaceaeNK4A214 [OR = 0.72, 95% CI (0.57,0.89), P = 0.003] were negative. Meanwhile, we also found that Betaproteobacteria [OR = 1.53, 95% CI (1.08,2.17), P = 0.017], cCoriobacteriaceae [OR = 1.39, 95% CI (1.07,1.80), P = 0.012], Eggerthella [OR = 1.34, 95% CI (1.12,1.61), P = 0.002], Burkholderiales [OR = 1.59, 95% CI (1.11,2.28), P = 0.011], Dorei [OR = 1.19, 95% CI (1.01,1.40), P = 0.038] and Dorea [OR = 1.09, 95% CI (1.00,1.18), P = 0.044] were positively correlated with CA, and there was a negative association between Bifidobacteriales [OR = 0.73, 95% CI (0.57,0.95), P = 0.018] and CA. Sensitivity analysis showed no facts of reverse causality, pleiotropy, and heterogeneity. Conclusions: Our study demonstrates that RuminococcaceaeUCG005 and Roseburia are related to an increased risk of AA, Prevotella9, and RuminococcaceaeNK4A214 can reduce the risk of AA. On the other hand, Coriobacteriaceae, Eggerthella, Burkholderiales, Dorei and Dorea are related to an increased risk of CA, Bifidobacteriales can reduce the risk of CA. In addition, gut microbiota may affect the occurrence of aneurysms through biomechanical mechanisms such as the elasticity and strength of blood vessel walls.